Psychoemotional disorders in cardiovascular patients: problem scope and diagnostics - R. G. Oganov; G. V. Pogosova; G. M. Dyukova; A. V. Fedotova (Кардиоваскулярная терапия и профилактика, 2005)
The article is devoted to high prevalence of psychoemotional and somatic (especially cardiovascular) disease association. Diagnostic criteria for most prevalent psychoemotional disorders (asthenic syndrome, anxiety, and depression) are reviewed.